Management of professional learning community model: A multi-site case study - Murdjoko Murdjoko; Wahyu Wahyu; Muhammad Saleh (Curricula: Journal of Curriculum Development, 2025)
Teacher-friendly learning communities represent a strategic approach to enhancing professionalism and collaboration among educators within schools. This study aims to describe and analyze the management of a teacher-friendly learning community model in terms of three main aspects: school leadership, teacher empowerment, and school partnerships. The research was motivated by the need to create a supportive learning ecosystem that fosters continuous professional development for teachers. A qualitative approach with a multi-site study design was employed, conducted at SMAN 1 Karang Intan and SMAN 2 Martapura, Banjar Regency. Data were collected through in-depth interviews, observations, and documentation involving principals, teachers, learning community leaders, subject group coordinators, and school staff. The findings indicate that school principals play an active managerial role in designing, facilitating, and evaluating learning community activities. Teachers responded positively to the empowerment provided, particularly through collaboration, pedagogical reflection, and improved teaching practices. Furthermore, internal and external partnerships—including collaboration with school staff, the education department, and teacher forums—contributed to the development of a learning ecosystem that supports the enhancement of teachers’ professional competencies. Nevertheless, several challenges remain, such as limited time, low intensity of peer observations, and weak coordination among stakeholders.    Abstrak Komunitas belajar ramah guru merupakan pendekatan strategis dalam meningkatkan profesionalisme dan kolaborasi antar guru di lingkungan sekolah. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis manajemen pengembangan model komunitas belajar ramah guru ditinjau dari aspek kepemimpinan kepala sekolah, pemberdayaan guru, dan kemitraan sekolah. Studi ini dilatarbelakangi oleh kebutuhan untuk menciptakan ekosistem belajar yang mendukung pengembangan kompetensi guru secara berkelanjutan. Pendekatan yang digunakan adalah kualitatif dengan desain studi multi situs, dilaksanakan di SMAN 1 Karang Intan dan SMAN 2 Martapura, Kabupaten Banjar. Teknik pengumpulan data meliputi wawancara mendalam, observasi, dan dokumentasi dengan melibatkan kepala sekolah, guru, ketua komunitas belajar, koordinator rumpun mata pelajaran, dan tenaga kependidikan. Hasil penelitian menunjukkan bahwa kepala sekolah memiliki peran manajerial yang kuat dalam merancang, memfasilitasi, dan mengevaluasi kegiatan komunitas belajar. Guru menunjukkan respons positif terhadap pemberdayaan yang dilakukan, terutama melalui kolaborasi, refleksi pedagogis, dan peningkatan praktik mengajar. Di samping itu, kemitraan internal dan eksternal, seperti kerja sama dengan tenaga kependidikan, dinas pendidikan, dan forum guru, turut memperkuat ekosistem belajar. Namun, beberapa tantangan yang dihadapi meliputi keterbatasan waktu, rendahnya intensitas observasi sejawat, serta lemahnya koordinasi antar pihak. Kata Kunci: kemitraan sekolah; kepemimpinan kepala sekolah; komunitas belajar; pemberdayaan guru